2018
DOI: 10.1111/joor.12642
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Karaduman Chewing Performance Scale in paediatric neuromuscular diseases: A system for classification of chewing disorders

Abstract: Chewing disorders can be seen in children with neuromuscular diseases (NMDs), which may cause swallowing difficulties such as choking, retching and food stuck feeling in the throat. Due to these effects, it is important to determine chewing disorders early with appropriate assessment methods to plan appropriate therapies in NMDs. The aim of this study was to investigate reliability and validity of the Karaduman Chewing Performance Scale (KCPS) in children with NMDs. Age, sex and diagnosis were recorded. Childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…Each item is rated on a 5-point Likert scale based on the frequency with which particular behaviors occur [ 40 ]. The Karaduman Chewing Performance Scale (KCPS) is a valid, reliable, quick, and clinically easy-to-use instrument to determine the level of chewing function in children [ 41 ]. The Tongue Thrust Rating Scale (TTRS) is the first and only scale that is valid, reliable, quick, and clinically easy-to-use to define tongue thrust severity in children [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each item is rated on a 5-point Likert scale based on the frequency with which particular behaviors occur [ 40 ]. The Karaduman Chewing Performance Scale (KCPS) is a valid, reliable, quick, and clinically easy-to-use instrument to determine the level of chewing function in children [ 41 ]. The Tongue Thrust Rating Scale (TTRS) is the first and only scale that is valid, reliable, quick, and clinically easy-to-use to define tongue thrust severity in children [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Karaduman Chewing Performance Scale (KCPS) is a valid, reliable, quick, and clinically easy-to-use instrument to determine the level of chewing function in children [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…It may be possible to ensure early detection of any problem in the stomatognathic system and needed consultation, by using a reliable and valid screening of the orofacial function in children (Marquezin et al, 2014). Most of the studies on this topic had been reported on a sample of the children with neurological or anatomical problems (Bergendal et al, 2014; Serel Arslan, Aydın, Alemdaroğlu, Tunca Yılmaz, & Karaduman, 2018; Serel Arslan, Kılınç, Yaşaroğlu, Demir, & Karaduman, 2018). Therefore, this study was conducted to show the OFD status and oral health status among healthy children.…”
Section: Discussionmentioning
confidence: 99%
“…Normal oral functions also contribute to maintaining oral health (Furuta & Yamashita, 2013). Valid, reliable, and clinically easy‐to‐use KCPS is an instrument that shows the chewing performance levels based on the order of functional movements during chewing (Serel Arslan, Aydın, et al, 2018). Chewing disorders and problems generally are characterized by long meal times, increased number of meals, late teething experience, fewer teeth existence, more problematic feeding behavior, and lack of oral motor functions (Gisel & Alphonce, 1995; Serel Arslan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a team of physiotherapists developed The Karaduman Chewing Performance Scale (KCPS) to determine via observation the overall level of chewing function in children with neuromuscular diseases ( Serel Arslan et al, 2016 ). The authors operationally defined chewing as a predictable sequence of movements from the first step of accepting food within the mouth to the final step of grinding and softening the food via a series of MC ( Serel Arslan et al, 2018 ). The scale was found to be a reliable and valid functional instrument to measure chewing ( Serel Arslan et al, 2018 ).…”
mentioning
confidence: 99%